How to sell your family to the aliens - North, Paul (New York : Bloomsbury, 2018)
Ten-year-old Hap's grandmother has experimented on his family and confined them to the basement of a mansion paid for by his father's inventions, but his plan to sell her to aliens goes awry.
Keywords: Family life -- Fiction; Grandmothers -- Fiction; Ability -- Fiction; Inventors -- Fiction; Extraterrestrial beings -- Fiction; Humorous fiction